Post-outbreak dynamics and persistence of Actinobacillus pleuropneumoniae serotype 15 in finisher pigs in Iowa - Marcelo Nunes de Almeida; Pablo P. Pineyro; Derald Holtkamp; Isadora Machado; Ana P. S. Silva; Guilherme Cezar; Peter Thomas; Marcelo Gottschalk; Alyona A. Michael (Veterinary Research)
Abstract In 2021, Actinobacillus pleuropneumoniae serotype 15 (App15) mediated a high mortality respiratory outbreak in finisher hogs, affecting multiple companies within a 30-km radius of Iowa, USA. The atypical regional spread raised concerns for the strain’s unusual environmental persistence and survivability. This prospective longitudinal study aimed to determine the duration of App15 persistence in convalescent pigs at a naturally infected 1200 head site. Sixty-seven pigs were sampled individually for 6 weeks using nasal swabs (NS), tonsil scrapings (TS), and serum samples (SS); pen-based oral fluids (OF) were also collected. NS, TS, and OF were tested for App by rtPCR, while serum was screened with the Swinecheck mix-App ELISA. All 67 pigs tested App PCR positive in TS ≥ 1 during the sampling period, with progressive increases in detection from 53.3% to 95.8% between the first and last sampling week, respectively. Only 23 pigs (34.3%) were PCR positive by NS ≥ 1 during the sampling period, with decaying detection rates from a peak of 51.2% positivity in the first sampling week. Fifty-three of 73 pens (72.6%) tested App PCR positive in OF ≥ 1 during the sampling period. Seropositivity decreased from 93% on week 4– to 33% on week 8. TS had the highest PCR detection rate at all time points evaluated, representing the best antemortem sample type for App PCR detection in this study. The results reported here generated new important knowledge related to App15 ecology and epidemiology, prospectively informing disease diagnosis, surveillance, and biosecurity practices.